الفِرق الإنشادية والمسرحية بوادي سُوف الجزائرية، ودورها الدّعويّ والاصلاحيّ ) 1977 – 1991) - شكيمة أحمد (University of Eloued جامعة الوادي, 2024)
تهدف هذه الدّراسة الى اهمية ومشروعية الفن الاسلامي وضروريته وحاجة الدعوة اليه والوقوف على اهم الفرق الإنشادية والمسرحية بوادي سوف الجزائرية وأهميتها ومدى مساهمتها في معالجة بعض القضايا الدعويّة و الاجتماعية المختلفة، في الفترة الممتدة ما بين 1977 إلى 1991، ثمّ التّعرف على آثارها في المجتمع، وخاصّة الشباب منهم، ومن ثمّ الوقوف على المتغيرات المعروضة في هذه الدراسة والمحرّكة لها في محاولة لمعرفة الدور الذي يساهم به فنّا النشيد والمسرح الإسلامي. وقد استعمل الباحث في دراسته المنهج التاريخي والوصفي، وكانت أداة الدراسة في الميدان التّطبيقيّ هي المقابلة، كما استفاد الباحث من الملاحظة من خلال متابعته في جمع المعلومات أثناء مقابلته لبعض ممّن عايش وعاصر تلك المدة الزّمنية. واشتملت الرّسالة على مقدّمةٍ وبيانٍ لمعاني الفن الاسلامي و الأنشودة والمسرح ، ثم التعريج على التّعريف بمنطقة وادي سُوف، الجنوب الجزائري، محل الدّراسة، ومعلومات عن فِرق الانشاد والمسرح المقصودة بالبحث وهي عشرة، خمسة منها مسحت بنشاطاتها معظم تراب الولاية، والخمسة الأخرى انحصرت نشاطاتها في مجال ضيّق. وفي الدّراسة طرح الباحث سبعة أسئلة على الفاعلين وحلّل وناقش الاِجابات، وختم الرّسالة بنتائج ثم توصيات من أبرزها ضرورة وأهمية التوثيق وكتابة الوقائع التاريخية القديمة وخاصة الثّقافية والفنية منها."This study aims at the importance and legitimacy of Islamic art, its necessity and the need to call for it, and to focus on the most important musical and theatrical groups in Wadi Souf, Algeria, their importance and the extent of their contribution to the treatment of various legal and social issues, in the period from 1977 to 1991, and then to recognize their works in society, especially Young people are among them, and then to focus on the variables presented in this study and the motivation for it in an attempt to find out the role that contributes to the art of song and theater The researcher used the historical and descriptive method in his study, and the tool of the study in the practical field was the interview, as well as the researcher used observation through observation to collect information during his interview with some of those who lived and lived in that period. The message included an introduction and a statement of the meaning of Islamic art, music, and theater, followed by an introduction to the area of Wadi Souf, southern Algeria, the place of study, and information about the difference between singing and theater. There are ten in question, five of which are related to the activities of the majority of the state, and the other five are limited to a narrow area of activity. In the study, the researcher posed seven questions to the participants, analyzed and discussed the answers, and then presented the results with recommendations.
Keywords: الفرق الإنشادية والمسرحية ، وادي سوف ، الدور الدعوي والاصلاحي، الفن الاسلامي; Choral and theatrical groups; Wadi Souf; advocacy and reform role; Islamic art